The Effect of Diabetes Self-management Education Provided by Certified Diabetes Educator Compared to Usual Diabetes Education on Glycemic Level and Stage of Behavior Change in Adult with Types 2 Diabetes Mellitus - Wongmuan, Kanyarat; Thanaboonsutti, Narinnad; Ketpan, Wilawan; Uprarat, Sarawoot; Lapinee, Varisara; Preechasuk, Lukana (Siriraj Medical Journal, 2024)
Objective: To explore the effect of diabetes self-management education and support (DSMES) provided by Siriraj certified diabetes educators (CDE) compared to usual diabetes education (DE) on glycemic level and stage of behavior change in patients with type 2 diabetes mellitus (T2D). Materials and Methods: Patients with T2D having A1C 8-12% were recruited between 2019-2020 to receive DSMES from CDE. Patients received the usual DE from healthcare professionals in 2016 were randomly selected from their medical records. Results: 76 patients were enrolled in each group. Mean±SD age was 59.4±11.5 years. After receiving DSMES and DE, A1C decreased dramatically at 3 months in both groups without significant difference between the groups (9.4±1.1% to 8.0±1.2% vs. 9.5±1.1% to 8.1±1.5%, respectively). However, the DEMES group can further decrease A1C to 7.8±1.2% while A1C in the usual DE group increased to 8.5±1.6% at 12 months (p=0.028). In the DSMES group, most patients can move to the next stage of behavior change and reported a better QOL (89.4±11.6 vs. 92.6±12.2, p=0.018). Conclusion: The receipt of DSMES from CDE significantly improved the level of A1C, the stage of behavior change, and QOL. Its benefit on the glycemic level can last at least one year.